Fetal transcerebellar diameter nomogram in Nepalese population - Joshi, BR (Journal of Institute of Medicine Nepal, 2010)
Introduction: Sonographic determination of gestational age (GA) is becoming increasingly important. Many parameters can be used for establishing GA. The transverse cerebellar diameter (TCD) is a reliable parameter for estimating it. Fetal cerebellum grows progressively along with GA and can predict GA at any trimester. This study was undertaken to construct an institution specific Transcerebellar diameter (TCD) nomogram and to compare its ability to predict gestational age with previously published nomograms. Methods: A cross-sectional nomogram was constructed using TCD measurements of 594 singleton fetuses in Nepalese population by using linear regression model. Measurements were obtained by placing the calipers of the ultrasound machine at the outer – to- outer margins of the cerebellum. The suitability of previously established TCD nomograms for predicting gestational age was assessed in Nepalese population to determine comparability between nomograms. Results: Gestational age and TCD 50th percentile in mm coincided well till 20th week of gestation. Between 21st to 28th weeks of gestation, there were no clinically important differences between our nomogram and previously published in terms of the predicted gestational age. However, predicted gestational age in third trimester was considerably different by using our nomogram by 1-2 weeks from 29-32 weeks and by 3-6 weeks after 33 weeks. There were differences of 4-6 mm between 29-32 weeks and of 7-11 mm after 33 weeks. Conclusions: TCD measurements had a similar relationship with gestational age across previously published nomograms before 28 weeks. Significant differences occurred in predicting gestational age after 33 weeks. DOI: http://dx.doi.org/10.3126/joim.v32i1.3997 Journal of Institute of Medicine, April, 2010; 32:1 pp.19-23